Unjuk Kerja Charge Controller metode PWM Menggunakan Arduino Uno - Hendi Matalata; Asnal Effendi (Jurnal Teknologi, 2022)
The need for a charge controller for the use of electrical energy sourced from solar panels and DC generators is very necessary for the purposes of the battery function as electric power in the inverter which functions as a voltage source. Usually the battery is used for inverter purposes in meeting household electricity needs as a substitute for PLN. The charging process will occur if the output voltage from the DC voltage source is higher than the battery voltage to be recharged. In this study, the charging process is based on PWM settings, and consists of 2 types, namely boost mode and float mode which are distinguished from the duty cycle setting. The voltage reading on the voltage divider sensor using a resistor has an error of less than 6.22% at the source terminal, and 6.89% at the battery. However, the charging process is able to provide an average voltage of 13.14 Volts on the battery (12 Volts), so that the charging process can run well.